Five-year conditional relative survival up to 10 years post-diagnosis among adolescent and young adult breast cancer patients by age, stage, and receptor subtype - Noëlle J.M.C. Vrancken Peeters; Daniël J. van der Meer; Marleen Kok; Marissa C. van Maaren; Marie-Jeanne T.F.D. Vrancken Peeters; Sabine Siesling; Winette T.A. van der Graaf; Olga Husson (Journal of the National Cancer Center)
Background: Conditional relative survival (CRS), the probability of survival given that an individual has already survived a certain period post-diagnosis, is a more clinically relevant measure for long-term survival than standard relative survival (RS). This study aims to evaluate the 5-year CRS among adolescent and young adult (AYA) breast cancer patients by age, tumor stage, and receptor subtype to guide disclosure periods for insurance. Methods: Data of all females aged 18–39 years and diagnosed with invasive breast cancer between 2003 and 2021 (n = 13,075) were obtained from The Netherlands Cancer Registry (NCR). The five-year CRS was calculated annually up to 10 years post-diagnosis using a hybrid analysis approach. Results: For the total AYA breast cancer study population the 5-year CRS exceeded 90 % from diagnosis and increased beyond 95 % 7 years post-diagnosis. Patients aged 18–24 reached 95 % 9 years post-diagnosis, those aged 25–29 after 5 years, and those aged 30–34 and 35–39 after 8 years. For stage I, the 5-year CRS reached 95 % from diagnosis, for stage II after 6 years, while the 5-year CRS for stages III and IV did not reach the 95 % threshold during the 10-year follow-up. Triple-negative tumors exceeded 95 % after 4 years, human epidermal growth factor receptor 2 (HER2) positive tumors after 6 years, while hormone receptor (HR) positive tumors did not reach 95 %. Conclusion: Excess mortality among AYA breast cancer patients tends to be little (CRS 90 %–95 %) from diagnosis and becomes minimal (CRS>95 %) over time compared to the general population. These results can enhance expectation management and inform policymakers, suggesting a shorter disclosure period.